Fablehaven - Mull, Brandon, 1974- (New York : Aladdin Paperbacks, 2007)
Kendra and Seth find themselves in the midst of a battle between good and evil when they visit their grandparents' estate and discover that it is a sanctuary for magical creatures.
5.0
5-8
5-8.
Kirkus Review
700
Keywords: Magic -- Fiction; Grandparents -- Fiction; Brothers and sisters -- Fiction; Magic -- Fiction; Grandparents -- Fiction; Siblings -- Fiction